Challenges in the development of cooperative-based closed-loop refined palm oil agribusiness in Indonesia - Sihombing, Luhut; Purwoko, Agus (Asian Journal of Agriculture and Rural Development, 2025)
There are marginal issues faced by independent palm oil farmers at the farm gate level and distortions in the downstream market, prompting the Ministry of Cooperatives and Small and Medium-sized Enterprises (SMEs) of Indonesia, the Palm Oil Fund Management Agency, and PTPN Group to pilot a program for downstreaming independent oil palms through cooperatives. The refined palm oil (RPO) program processes crude palm oil (CPO) using fractionation and soft refining without bleaching and deodorization. Its goal is to stabilize fresh fruit bunch (FFB) prices and provide affordable cooking oil alternatives. The government supports this initiative through regulations, constructing RPO plants, and allocating them to cooperatives.This study seeks to assess the planning, closed-loop RPO agribusiness development, and requisite strategies for its success. Using methods like Context, Input, Process, and Product (CIPP) and Analytical Hierarchy Process (AHP) for qualitative research shows that for the program to work at its best, separate palm oil crops must be used to match the capacities of RPO plants. Furthermore, government subsidies are crucial because of the elevated manufacturing costs of RPO relative to CPO. Moreover, continuous branding initiatives by the government and cooperatives are essential to improve public acceptance and commercial visibility. Some of the strategies that could be used to support the success of the program include building and granting oil palm processing (OPP) plants to cooperate for independence; certification of Roundtable on Sustainable Palm Oil (RSPO) on all independent palm oil plantations; and application of more efficient processing technology technically and economically so that the product could compete with other commercial palm oil products.